Using Chronological Order Method to Improve Writing Ability of the Third Year Students of SMA Negeri I Pangsid Kabupaten Sidenreng Rappang - Roni Roni (EDUVELOP, 2018)
The objective of the research was to find out whether or not using chronological order was able to improve writing ability of the students of SMA Negeri 1 Pangkajene Sidrap. This study employed pre-experiment method, using the third year students of SMA Negeri 1 Pangsid kabupaten Sidenreng Rappang in Academic year 2011/2012. Total number of population was 192 students on six classes one of them were taken as sample by using cluster random sampling technique; class IPA 1 consisting 32 students. The instrument used in this research was to chronological order. The research used an experimental design one class was given pre-test, treatment and post-test design. The population was the third students of SMA Negeri 1 Pangsid kabupaten Sidenreng Rappang in academic year 2011/2012. The sample of this research was third year of SMA Negeri 1 Pangsid Kabupaten Sidenreng Rappang there were 32 students. The technique of sampling was cluster random sampling, and the data was analyzed into percentage, mean score analyzes and the of the research shows that teaching writing by using chronological order can increase the writing ability of the third year students of SMA Negeri 1 Pangsid kabupaten Sidenreng Rappang in which the result of t-test ( 5.743) is higher than t-table (2.042) with df( N-1) =32-1=31 in the level of significance ( 0.05) = 2.042. It means that using chronological order method in teaching writing is able to improve writing ability of the third year students of SMA Negeri 1 Pangsid Kabupaten Sidenreng Rappang.